2002
DOI: 10.1103/physrevd.66.103002
|View full text |Cite
|
Sign up to set email alerts
|

Neutrino bounds on astrophysical sources and new physics

Abstract: Ultra-high energy cosmic neutrinos are incisive probes of both astrophysical sources and new TeV-scale physics. Such neutrinos would create extensive air showers deep in the atmosphere. The absence of such showers implies upper limits on incoming neutrino fluxes and cross sections. Combining the exposures of AGASA, the largest existing ground array, with the exposure of the Fly's Eye fluorescence detector integrated over all its operating epochs, we derive 95% CL bounds that substantially improve existing limi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
333
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 180 publications
(338 citation statements)
references
References 112 publications
(72 reference statements)
4
333
1
Order By: Relevance
“…The region with the solid boundary is obtained by a cosmological evolution parameter n = 3. Boxes show the upper bounds obtained by combining Fly's Eye [13] and Agasa [14] limits on deeply penetrating showers in different energy bins [15]. According to these limits, strong cosmological evolution (n > 3) for the sources of the post-GZK events is already excluded.…”
Section: Propagation Inversionmentioning
confidence: 99%
See 2 more Smart Citations
“…The region with the solid boundary is obtained by a cosmological evolution parameter n = 3. Boxes show the upper bounds obtained by combining Fly's Eye [13] and Agasa [14] limits on deeply penetrating showers in different energy bins [15]. According to these limits, strong cosmological evolution (n > 3) for the sources of the post-GZK events is already excluded.…”
Section: Propagation Inversionmentioning
confidence: 99%
“…The variation due to the change of this parameter between 0 and 6 is also shown. Present [15] and expected [16] experimental bounds by AGASA, Fly's Eye and Auger, respectively, are also presented.…”
Section: Propagation Inversionmentioning
confidence: 99%
See 1 more Smart Citation
“…A eff , T live and ε are all energy dependent. Methods set out in [77,92,105] show that equation 8.1.1 underestimates the limit that can be placed on the UHE neutrino flux. Equation 8.1.1 effectively places an upper limit on the flux at any given neutrino energy for the number of events observed, while the desired limit should account for neutrino flux models providing neutrinos over the energy interval being considered.…”
Section: Diffuse Uhe Neutrino Flux Limitmentioning
confidence: 99%
“…One could thus claim with confidence that black holes with masses 5 to 20 times the Planck scale, depending on the model of quantum gravity, could form in the collision of particles at the CERN LHC is the Planck scale was low enough. Early phenomenological studies can be found in [8][9][10][11][12][13][14]. …”
mentioning
confidence: 99%